MODEL AND INTERACTIVE METHODS OF DEVELOPING STUDENTS' CREATIVITY IN COMPOSITION (Web of Teachers: Inderscience Research, 2026)
The article presents a model for developing students' creativity through modern methodologies in teaching composition. The four-block pedagogical model architecture (motivational-purposive, content, procedural-technological, result-diagnostic), didactic capabilities of interactive methods, and integration of Western and Eastern pedagogical approaches are covered. Research findings scientifically substantiate the role of interactive methods (visual framing, case studies, reconstruction, brainstorming, reflective discussion) in developing compositional creativity.